2020
DOI: 10.1002/jbmr.4726
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Parathyroid Hormone Replacement With TransCon PTH in Hypoparathyroidism: 26-Week Results From the Phase 3 PaTHway Trial

Abstract: Conventional therapy for hypoparathyroidism consisting of active vitamin D and calcium aims to alleviate hypocalcemia but fails to restore normal parathyroid hormone (PTH) physiology. PTH replacement therapy is the ideal physiologic treatment for hypoparathyroidism. The double-blind, placebo-controlled, 26-week, phase 3 PaTHway trial assessed the efficacy and safety of PTH replacement therapy for hypoparathyroidism individuals with the investigational drug TransCon PTH (palopegteriparatide). Participants (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 31 publications
0
31
0
1
Order By: Relevance
“…TransCon PTH was safe and effective and well tolerated over 26 weeks. (109) These results support TransCon PTH as a potential hormone-replacement therapy for adults with HypoPT. (106) Open-label trials have reported improvements in QoL with both rhPTH (1-84) (72,73,110) and PTH (1-34).…”
Section: Emergency Management Of Severe Acute Hypocalcemiamentioning
confidence: 57%
“…TransCon PTH was safe and effective and well tolerated over 26 weeks. (109) These results support TransCon PTH as a potential hormone-replacement therapy for adults with HypoPT. (106) Open-label trials have reported improvements in QoL with both rhPTH (1-84) (72,73,110) and PTH (1-34).…”
Section: Emergency Management Of Severe Acute Hypocalcemiamentioning
confidence: 57%
“…Nachfolgepräparate, insbesondere das sog. TransCon PTH, befinden sich allerdings in der Vorbereitung und klinischen Prüfung [13].…”
Section: Spezifische üBerlegungenunclassified
“…Studies with PTH (1-84) therapy demonstrated significant improvements in QoL (49) and this was also observed with the TransCon PTH molecule which has a 60-hour half-life and is currently in phase 3 trials. (50)…”
Section: Pth Therapy In Comparison To Conventional Therapymentioning
confidence: 99%
“…No study drug-related withdrawals occurred. (86) An injectable long-acting PTH analogue (LA-PTH), a hybrid molecule with both PTH and PTHrP homology, increased serum calcium and reduced serum phosphorus in a thyroparathyroidectomized rat model of HypoPT and had prolonged effects on serum calcium in monkeys. (87,88) Phase-1 trial data with this drug, AZP-3601, has been presented.…”
Section: Emerging Therapies For Hypoptmentioning
confidence: 99%